ANALISIS TINGKAT KETERAMPILAN GENERIK SAINS SISWA KELAS XI-MIA SMA NEGERI 8 PEKANBARU PADA MATERI KALOR DAN PERPINDAHANNYA - Reca Sintya Mawarni; Yennita Yennita; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was aimed to describe the level of sains generic skill at the second year students of MIA program of SMA 8 Pekanbaru toward student’s competency of calor material and it’s movement. This research was a survey research. The result of the data analysis used descriptive analysis which described the level of student’s sains generic skill. The subject of this research was 76 students of MIA program at the second year. The data gotten from this research was in average percentages of the student’s level of sains generic skill in solving the physics phenomenon. This instrument was developed based on the indicators of sains generic skill. Then, the data was categorized based on the level of sains generic skill category namely directly observation, non-directly observation, language symbolic, logical inference, cause effect relationship, modeling of math, awareness of big scale, and concept construction. Based on the data analysis showed that the average percentages of each indicators as follows: 75,72% for directly observation, 47,07 % for non-directly observation, 69,01 % for language symbolic, 78,91 % for logical inference, 68,13 % for cause effect relationship, 69,54 % for modeling of math, 58,49 % for awareness of big scale, and 65,07 % for concept construction. The overall percentages of the students’ generic sains skill was 67,16% categorized into high level. The highest percentage was 72, 37 % and the lowest percentage was 27,63%.Key words: Sains generic skill, Solving problem, Logical thinking.